A Brief History of Biomedical Research Ethics in Iran: Conflict of Paradigms. Issue 2 (11th April 2014) - Aramesh, Kiarash
Abstract During the past two decades, Iran has experienced a noteworthy growth in its biomedical research sector. At the same time, ethical concerns and debates resulting from this burgeoning enterprise has led to increasing attention paid to biomedical ethics. In Iran, Biomedical research ethics and research oversight passed through major periods during the past decades, separated by a paradigm shift. Period 1, starting from the early 1970s, is characterized by research paternalism and complete reliance on researchers as virtuous and caring physicians. This approach was in concordance with the paternalistic clinical practice of physicians outside of research settings during the same period. Period 2, starting from the late 1990s, was partly due to revealing of ethical flaws that occurred in biomedical research in Iran. The regulatory and funding bodies concluded that it was not sufficient to rely solely on the personal and professional virtues of researchers to safeguard human subjects' rights and welfare. The necessity for independent oversight, emphasized by international declarations, became obvious and undeniable. This paradigm shift led to the establishment of research ethics committees throughout the country, the establishment of academic research centers focusing on medical ethics (MEHR) and the compilation of the first set of national ethical guidelines on biomedical research–one of the first and most important projects conducted by and in the MEHR. Although not yet arrived, 'period 3' is on its way. It is predictable from the obvious trends toward performance of high‐quality clinical research and the appearance of a highly educated new generation, especially among women.